[Rezension von: Bond, Helen K., 1968-, The first biography of Jesus : genre and meaning in Mark's gospel] - Heijer, Arco den 1989-; Bond, Helen K. 1968- (2021)
Helen Bond reads the Gospel of Mark alongside other ancient biographies. She argues that Mark depicts Jesus as a teacher who calls his disciples to serve, and who dies in a way that corresponds with his teaching. The book provides numerous insights into the meaning of the Gospel and the literary skills of its author. It is warmly recommended.
Helen Bond liest das Markusevangelium zusammen mit anderen Biographien der Antike. Sie argumentiert, dass Markus Jesus als einen Lehrer darstellt, der seine Jünger dazu beruft zu dienen und der auf eine Weise stirbt, die seiner Lehre entspricht. Das Buch gibt zahlreiche Einblicke in die Bedeutung dieses Evangeliums und die literarischen Fähigkeiten seines Autors. Es ist wärmstens zu empfehlen.
Helen Bond lit l’Évangile de Marc en parallèle avec d’autres biographies anciennes. Sa thèse est que Marc décrit Jésus comme un enseignant qui appelle ses disciples au service et meurt d’une façon conforme à son enseignement. Le livre jette une belle lumière sur le sens de l’évangile et les dons littéraires de son auteur. On ne peut que le recommander vivement.
Keywords: Rezension